Kreativitas Pengelola BUMDES Desa Sipatuhu dalam Mempromosikan Produk Makanan Olahan melalui Website - Bambang Sulistyo; Hendra Alfani; Akhmad Rosihan; Alip Susilowati Utama (Universitas Mathla'ul Anwar Banten, 2020)
CREATIVITY OF SIPATUHU VILLAGE BUMDES MANAGEMENT IN PROMOTING PROCESSED FOOD PRODUCTS THROUGH THE WEBSITE. Empowerment of village communities based on the superior potential of the village is the key to increasing welfare and community independence. Sipatuhu Village, Banding Agung Subdistrict, Ogan Komering Ulu Selatan District, South Sumatra Province, has a potential that other villages do not have. Sipatuhu village has abundant potential for plantation resources, namely robusta coffee and palm sugar, the largest in South Sumatra. The Village Government, Village-Owned Enterprise Managers, and elements of the Sipatuhu Village community are working together to improve the potential management capacity so that it has high economic value. In addition to increasing the capacity of village productive economic governance, creative efforts were also made to innovate in designing promotional media and marketing of products in the form of processed robusta coffee, and sugar and liquid palm sugar made from palm sap, through the website. The use of information technology was chosen to expand the product marketing reach to potential consumers, if previously it was still done conventionally. This effort has produced positive results, although it is still simple, the website as a promotional medium has been successfully realized, by developing both the views on the website design, as well as the narrative and promotional content displayed.